Diameter measurements in three-dimensional printed flow phantom model of the carotid artery in preterm infants - Pereira, Sujith; Reeves, Jonathan; Birch, Malcolm; Ali, Ahmed; Sinha, Ajay; Kempley, Stephen (British Journal of Healthcare and Medical Research, 2021)
Diameter form an integral part of blood flow measurement. This study aimed to explore different three-dimensional (3D) printed materials to develop flow phantom models of the carotid artery in preterm newborn infants and to investigate ideal diameter measurement points using ultrasound that reflected accurate lumen diameter measurement. Cerebral blood flow measurements data using Doppler ultrasound of the right common carotid artery from 21 randomly selected preterm infants were used to produce a 3D printed Doppler flow phantom model with three different vessel diameters. Diameters were measured by multiple observers blinded to phantom vessel characteristics and each other’s measurements. 9 measurement points were studied. Agreement between observers, inter and intra observer reliability and coefficient of variation (CoV) was examined. Of the 63 diameter measurements, 45 (71%) were performed on flow phantoms with vessel diameter of 0.196 cm. Bland-Altman plots revealed that measurement performed using leading edge to centre (mean bias 1.8% {95%LOA -4.1% to 7.7%}) and centre to trailing edge (mean bias 1.1% {95%LOA -5.4% to 7.8%}) resulted in the most accurate lumen diameter measurements. Inter and intra-observer reliability was excellent. The mean CoV for inter observer measurements was 1.7% and intra observer measurements was 1.6% and 1.8% for each observer. We successfully produced a 3D printed flow phantom model of the carotid artery in preterm infants and identified two measurement methods that result in reliable and accurate lumen diameter measurement. Researchers and clinicians can use this information for further studies involving ultrasound diameter measurements in small calibre vessels.